Synthesis and crystal structure of a meso-trialkynyl[28]hexaphyrin. - Krivokapic, A; Anderson, H (2003)
A 5,15,25-trialkynyl [28]hexaphyrin(1.1.1.1.1.1) is the main product of the boron trifluoride-catalysed condensation of meso-anthryl dipyrromethane and triisopropylsilylpropynal; it absorbs strongly in the near-infrared, out to 1093 nm.